2017
DOI: 10.1104/pp.17.01183
|View full text |Cite
|
Sign up to set email alerts
|

Carnosic Acid and Carnosol, Two Major Antioxidants of Rosemary, Act through Different Mechanisms

Abstract: Carnosic acid, a phenolic diterpene specific to the Lamiaceae family, is highly abundant in rosemary (Rosmarinus officinalis). Despite numerous industrial and medicinal/pharmaceutical applications of its antioxidative features, this compound in planta and its antioxidant mechanism have received little attention, except a few studies of rosemary plants under natural conditions. In vitro analyses, using high-performance liquid chromatography-ultraviolet and luminescence imaging, revealed that carnosic acid and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
110
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(139 citation statements)
references
References 54 publications
8
110
0
1
Order By: Relevance
“…Among the quantified compounds (Tables and ), carnosic acid was the second most abundant phenolic compound in rosemary and the crude LE extracts contained significantly higher concentrations (535.5 ± 77.3 mg/100 g DW) in comparison to the MI (298.3 ± 40.5 mg/100 g DW). Previous studies have also shown that the rosemary leaves have high content of carnosic acid (Birtić, Dussort, Pierre, Bily, & Roller, ; Loussouarn et al, ). Decolorization with activated charcoal did not significantly affect the concentration of the compound in LE crude extracts, but it led to a significant reduction in the case of MI.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Among the quantified compounds (Tables and ), carnosic acid was the second most abundant phenolic compound in rosemary and the crude LE extracts contained significantly higher concentrations (535.5 ± 77.3 mg/100 g DW) in comparison to the MI (298.3 ± 40.5 mg/100 g DW). Previous studies have also shown that the rosemary leaves have high content of carnosic acid (Birtić, Dussort, Pierre, Bily, & Roller, ; Loussouarn et al, ). Decolorization with activated charcoal did not significantly affect the concentration of the compound in LE crude extracts, but it led to a significant reduction in the case of MI.…”
Section: Resultsmentioning
confidence: 89%
“…Carnosic acid is present exclusively in some species of the Lamiaceae family, such as rosemary, while other spices such as thyme tend to accumulate carnosol rather than carnosic acid (Loussouarn et al, ). Among the quantified compounds (Tables and ), carnosic acid was the second most abundant phenolic compound in rosemary and the crude LE extracts contained significantly higher concentrations (535.5 ± 77.3 mg/100 g DW) in comparison to the MI (298.3 ± 40.5 mg/100 g DW).…”
Section: Resultsmentioning
confidence: 99%
“…Carnosic acid and carnosol contain a single aromatic ring with two −OH groups that can serve as H* donors and can also chelate pro‐oxidative metals, thus preventing oxidation via two mechanisms (Brewer, ). Furthermore, carnosic acid is a reactive oxygen species quencher (Loussouarn et al ., ). However, a synergistic effect from the antioxidant compounds present in rosemary is more likely since rosemary extracts demonstrate higher antioxidant activity than do the individual phenolic compounds separately (Brewer, ).…”
Section: Resultsmentioning
confidence: 97%
“…Phenolic diterpenes (carnosol, carnosic acid) are the main antioxidant compounds found in rosemary plant. These compounds exert their antioxidant activity through different mechanisms (Loussouarn et al ., ). The findings of the present study suggest that compounds present in rosemary can prevent lipid oxidation of vegetable oils by acting as secondary antioxidants and stabilising indigenous antioxidants such as tocopherols and carotenoids.…”
Section: Resultsmentioning
confidence: 97%
“…Levels of carnosic acid and carnosol were available for dried rosemary leaves (112 mg/kg (Loussouarn et al, 2017)), fresh rosemary leaves (12.18 mg/kg (Luis and Johnson, 2005)) and dried sage (5.3 mg/kg (FooDB version 1.0 database 21 )). Levels of carnosic acid and carnosol were available for dried rosemary leaves (112 mg/kg (Loussouarn et al, 2017)), fresh rosemary leaves (12.18 mg/kg (Luis and Johnson, 2005)) and dried sage (5.3 mg/kg (FooDB version 1.0 database 21 )).…”
Section: Exposure Via the Regular Dietmentioning
confidence: 99%